Engagement of Latino immigrant men who have sex with men for HIV prevention through eHealth: preferences across social media platforms. Issue 7 (3rd October 2022) - Lee, Jane J.; Aguirre, Joel; Munguia, Lesster; Robles, Gabriel; Ramirez Hernandez, Kenia; Ramirez, Jessica I.; Leyva Vera, Christopher A.; Duran, Miriana C.
ABSTRACT: Objective: eHealth has growing potential to enhance access to HIV prevention for hard to reach populations, including young Latino immigrant men who have sex with men (MSM) in the United States. We examined the feasibility and acceptability of using eHealth tools, specifically social media platforms, to facilitate HIV testing and pre-exposure prophylaxis (PrEP) uptake among this population. Design: We utilized a community sensitive approach to conduct 30 in-depth interviews and five focus groups with young Latino immigrant MSM in Seattle, WA. Data were analyzed using thematic analysis with both data-driven inductive and a priori deductive approaches. Results: Participants were open to receiving HIV information via social media platforms. Participants recommended that social media content be tailored with their language preferences, cultural norms, and beliefs about HIV testing and PrEP in mind. Further, participants emphasized that content avoid stigmatizing HIV or Latino MSM's complex identities. Conclusions: Results have implications for utilizing social media platforms and developing HIV prevention interventions for Latino immigrant MSM. Findings highlight that HIV prevention content should acknowledge how identities as an emerging adult, Latino, immigrant, and MSM, warrant unique consideration.